The Concept of Technology-Based Folk Poetry Learning Media Based on the Experience of Indonesian Language Teachers in West Sumatra (Konsep Media Pembelajaran Puisi Rakyat Berbasis Teknologi berdasarkan Pengalaman Guru Bahasa Indonesia di Sumatra Barat) - Yosi Wulandari; M. Ardi Kurniawan; Denik Wirawati; Nuril Anwar; Mohammad Argi Arifandi (Jurnal Gramatika, 2023)
The best learning is a learning process that is supported by the application of functional learning tools. With the development of needs in the world of education with the global era, significant learning is designed by adjusting to the era of students familiar with technology. However, it is not easy for teachers to move to make full use of various technologies with various limitations. This study aims to present conceptual technology-based learning media based on the experience of junior high school teachers in West Sumatra in learning folk poetry with a qualitative research approach. The respondents in this study were ten teachers who were determined based on the purposive sampling method.  Data were obtained through in-depth interviews with individual teachers. Interview data was analyzed with a content analysis approach to content analysis. This study found that technology-based learning media is a learning aid that utilizes technology, namely using projectors as tools, using YouTube videos, utilizing music, musicalization, and making videos uploaded on social media and YouTube. The interview results showed that teachers who mastered the concept of technology media were found to be able to innovate learning media to increase the success and achievement of learning and could strengthen the character, culture, and profile of Pancasila